Integrating Indigenous Knowledge Systems (IKS) to climate change adaptation in South Africa: Lessons from the "past" - Madzivhandila, T. S. (South African Journal of Higher Education, 2024)
For a long period of time, what is termed scientific knowledge and discoveries have constantly ignored the existence of indigenous practices and knowledge. Until recently, indigenous knowledge systems (IKS) were not acknowledged when it comes to responding to the ailing world. IKS includes information created inside inborn social orders, autonomous of, and earlier to, the appearance of the cutting-edge logical information framework. It can relate to issues such as conserving nature, food production, forestry development and medicine, to mention a few. The purpose of the article is to discuss the importance of the integration of IKS and culture into climate change adaptation. This article makes the case that scientific interventions among the impoverished in rural developing nations are viewed as foreign and are thus not accepted by the local populace. Consequently, the scientific approach by development experts, and the complex nature of climate change and its understanding, has had no impact on people’s adaptation in rural areas, where most of the people still rely on IKS to survive. This theoretical article focuses on the implications of IKS for climate change adaptation. The question the article intends to answer is, with the advent of climate change in recent years, how are rural communities coping with its impact? How is the scientific understanding of climate change with its complexities filtering down to the indigenous communities’ coping and adaptation activities? The article’s conclusion demystifies the notion that the impact of climate change might be mitigated, and repair achieved solely by scientifically developed measures against it. The article intends to contribute towards building knowledge that acknowledges the importance of different sources of interventions towards addressing climate change. It is important for the current and future professoriate to look beyond the conventional understanding of dealing with challenges such as climate change that the world is facing.